Controllable fabrication of novel all solid-state PbS quantum dot-doped glass fibers with tunable broadband near-infrared emission. Issue 31 (27th July 2017) - Huang, Xiongjian; Fang, Zaijin; Kang, Shiliang; Peng, Wencai; Dong, Guoping; Zhou, Bo; Ma, Zhijun; Zhou, Shifeng; Qiu, Jianrong
Abstract : Novel all solid-state PbS quantum dot-doped glass fibers with tunable near-infrared emissions were fabricated by using the "melt-in-tube" method. Abstract : All solid-state PbS quantum dot (QD)-doped glass fibers with tunable near-infrared (NIR) emission were successfully fabricated by using the "melt-in-tube" method for the first time. The precursor fibers were first prepared without any obvious element diffusion or crystallization by drawing the fiber preform at a heating temperature at which the fiber core was already melted while the fiber cladding was softened. Then the PbS QDs were precipitated evenly in the matrix of the glass fiber core after a careful heat treatment at low temperature. From the PbS QD-doped glass fibers, intense wavelength-tunable broad NIR emission bands were observed upon excitation with an 808 nm laser. The transmission loss of the fibers can be reduced by further matching the thermal expansion of the fiber core and cladding glass. Therefore, after further optimizing the composition and optical properties of the PbS QD-doped glass fiber, it is expected to be a potential gain medium for the development of wavelength-tunable lasers and broadband fiber amplifiers. More importantly, the melt-in-tube method exhibits a feature of completely controllable crystallization in the fiber formation process, which would open a new route for fabricating novel functional QD-doped glass fibers.